Model predictive cascade control - Zhang, Yu. (2008)
In this thesis, a state space Model Predictive Control (MPC) algorithm for multirate cascade control is discussed in detail. An appropriate choice of the cost function is necessary to ensure zero steady state error of the closed loop system. In this thesis, the influence the estimation horizon has on the closed-loop disturbance rejection property and the robustness of the closed-loop system against modeling errors is investigated. The proposed multirate cascade control MPC algorithm is applied to a laboratory scale experiment apparatus, the coupled-tank.